"I Can be Who I Am When I Play Tekken 7": E-sports Women Participants from the Islamic Republic of Pakistan. Issue 8 (December 2021) - Hussain, Umer; Yu, Bo; Cunningham, George B.; Bennett, Gregg
Extant research on e-sports has focused on the growth and value of the phenomenon, fandom, and participant experiences. However, there is a paucity of e-sports scholarship detailing women's experiences from marginalized communities living in various conservative Muslim countries. This shortage of literature remains despite different radical Islamic groups' consistent demand for banning several online video games and the Muslim youth's resistance to these calls. This study aimed to understand the motives and lived experiences of Muslim women e-sports participants from Gilgit-Baltistan, Pakistan. The authors collected data via observations of online video games and in-depth interviews. The study participants revealed that they use e-sports as a vehicle for an oppositional agency and personal freedom from the patriarchal system. The findings also suggest that participants are facing systematic marginalization and grave intrusion of post-colonization. The study contributes to the limited scholarship concerning Indian subcontinent Muslim women's e-sports participation.